Gibbs free energy of formation of Cu2In2O5 ternary phase determined by E.M.F. method - Jendrzejczyk-Handzlik, Dominika; Handzlik, Piotr (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Employing electrochemical cells with the solid zirconia electrolyte: Cu2O,CuO /O2- / air Cu2In2O5, In2O3,Cu2O / O2-/ air In,In2O3 /O2-/ Ni, NiO Gibbs free energy of formation of solid Cu2In2O5 phase as well as that for In2O3 and CuO oxides was determined in the temperature range from 973 K to 1372 K. The results obtained in this study were used to derive Gibbs free energy change of the reaction of formation of the ternary compound from respective oxides: 2CuO + In2O3 = Cu2In2O5 which is equal to: (±1400 J/mol). Oxygen potential diagrams for the Cu–In–O system are also given at two temperatures.